Как Бабы-Яги сказку спасали - Мокиенко Михаил Юрьевич (Новые сказочные повести, 2016)
Экземпляры: СБ (20171101) / Инвентарный номер: 54873 / Цена: 97.00 / Сис.шифр: Р2ср / Авт.знак: М 74 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6